A Preliminary Study of Ecosystems and Biodiversity in Lonar Crater - Jha, Mohan (Indian Forester, 2003)
The Lonar crater , situated in Buldhana Forest Division in Maharashtra , is a unique ecosystem in the world. It is believed that Lonar crater has been formed around 50 ,000 years ago by the impact of a large meteorite about 60 m across and a million tonnes in weight. It is an isolated deep saucer like depression nearly circular in shape and surrounded on all sides by steeply rising embankment to a height of 130 m. The presence of brackish water lake inside the crater having pH around 10 to 11 is a distinctive feature of the ecosystem. Fresh water springs on the slopes of the crater is another remarkable feature , which supports rich biodiversity inside the crater. Lonar crater is having many micro-ecosystems with fascinating biodiversity. However , no systematic study has been conducted on ecological aspects of this crater. Some preliminary observations in this regard indicate that there exist about nine micro-ecosystems , about fourteen types of blue green algae , five types of alkaliphilic bacteria , 57 birds’ species , and variety of reptiles , mammals , snakes , bats and colourful butterflies. About 237 plant species belonging to 153 genera and representing 70 families have been recorded in the Lonar crater. Richness of biodiversity is evident from the presence of 128 herbs , 30 shrubs , 5 under shrubs , 19 climbers and 57 trees in the crater. Further detail investigation in various ecological aspects of the crater is recommended.